2016
DOI: 10.1016/j.ccell.2016.03.027
|View full text |Cite
|
Sign up to set email alerts
|

Olig2-Dependent Reciprocal Shift in PDGF and EGF Receptor Signaling Regulates Tumor Phenotype and Mitotic Growth in Malignant Glioma

Abstract: Summary Malignant gliomas exhibit extensive heterogeneity and poor prognosis. Here we identify mitotic Olig2-expressing cells as tumor-propagating cells in proneural gliomas, elimination of which blocks tumor initiation and progression. Intriguingly, deletion of Olig2 resulted in tumors that grow, albeit at a decelerated rate. Genome occupancy and expression profiling analyses reveal that Olig2 directly activates cell proliferation machinery to promote tumorigenesis. Olig2 deletion causes a tumor phenotypic sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
127
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(139 citation statements)
references
References 37 publications
10
127
1
1
Order By: Relevance
“…We confirmed specificity and effects of shRNA-mediated knockdown by utilizing three alternate hairpins targeting the human OLIG2 ORF (Figure S3B). In contrast to recent findings (Lu et al, 2016), we did not observe a parallel up-regulation of EGFR protein following acute silencing of OLIG2 in PDGFRα HIGH hGSCs (Figure 3B and S3C). Furthermore, analysis of published OLIG2/H3K27ac ChIP-seq data in hGSCs (Suva et al, 2016), confirms OLIG2 binding at both distal and intronic enhancers at both the EGFR and PDGFRA loci (data not shown).…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…We confirmed specificity and effects of shRNA-mediated knockdown by utilizing three alternate hairpins targeting the human OLIG2 ORF (Figure S3B). In contrast to recent findings (Lu et al, 2016), we did not observe a parallel up-regulation of EGFR protein following acute silencing of OLIG2 in PDGFRα HIGH hGSCs (Figure 3B and S3C). Furthermore, analysis of published OLIG2/H3K27ac ChIP-seq data in hGSCs (Suva et al, 2016), confirms OLIG2 binding at both distal and intronic enhancers at both the EGFR and PDGFRA loci (data not shown).…”
Section: Resultscontrasting
confidence: 99%
“…Similar molecular subtype conversion findings were recently presented (Lu et al, 2016), however, these authors observed a “Proneural-Classical” subtype shift following Olig2 deletion. These authors employed a murine glioma model which initiates tumors in a very specific cell type (white matter OPCs) bearing mutations unique to the Proneural subtype ( Tp53;Pten deletion; Pdgfb over-expression), excluding the possibility of transformation in more naïve cells (i.e., neural stem/progenitor cells) and Olig2 functions therein (i.e., sustaining Egfr expression; Figure 2).…”
Section: Discussionsupporting
confidence: 89%
“…Importantly, these genes included five transcription factors ( OLIG1, OLIG2, ZEB1, ETV1, SOX6 ). Two of these transcription factors, OLIG2 and ZEB1, which we found associated with promoter-distal SOX2 bound regions ( Figures 2F and 2G ), have been suggested to be critical for GBM maintenance and propagation (Ligon et al, 2007; Lu et al, 2016; Mehta et al, 2011; Siebzehnrubl et al, 2013; Suva et al, 2014) and may be direct targets of SOX2 through promoter-distal cis -regulatory elements. Importantly, previous work demonstrated that silencing of ZEB1 in GBM cells resulted in attenuated expression of SOX2 and OLIG2, likely by repressing miR-200 microRNAs that target SOX2 and OLIG2 transcripts (Siebzehnrubl et al, 2013), which suggests that ZEB1 expression in GBM is critical for SOX2 and OLIG2 expression.…”
Section: Resultsmentioning
confidence: 79%
“…In our experiments, we set out to use patient-derived tumor cells with genetically defined malignancy drivers for siRNA targeting. Given that intratumoral heterogeneity is likely unavoidable (49,64,65), subpopulations of BTICs independent of TFs within the tumor would likely overtake the growth even if siRNA combination therapies are effective in suppressing the BTIC populations dependent on TFs (66,67). This likelihood leads to the prospect of further combined targeting of adaptive malignancy drivers in response to TF suppression as an additional strategy toward personalized precision medicine.…”
Section: Discussionmentioning
confidence: 99%